2016
DOI: 10.1186/s40792-016-0229-3
|View full text |Cite
|
Sign up to set email alerts
|

Solitary left axillary lymph node metastasis after curative resection of carcinoma at the colostomy site: a case report

Abstract: BackgroundThe incidence of axillary lymph node metastasis (ALNM) of colon cancer is very low, and there have been only a few reports of solitary ALNM. Neither the mechanism involved in solitary colon cancer ALNM nor the proper treatment has been elucidated. We encountered a case of solitary left ALNM after curative resection of carcinoma at the colostomy site.Case presentationA 53-year-old man underwent a Hartmann’s operation for Hirschsprung disease during his adolescence. He complained of a mass of the desce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Given the low incidence of stoma site tumors, the management protocol is unknown. Indeed, no previous studies have examined the need to add chemotherapy pre-or post-operatively, although adjuvant chemotherapy is recommended in some case reports [7,12,13,15]. In our group, postoperative adjuvant chemotherapy was recommended for all patients, but compliance was not high.…”
Section: Discussionmentioning
confidence: 80%
“…Given the low incidence of stoma site tumors, the management protocol is unknown. Indeed, no previous studies have examined the need to add chemotherapy pre-or post-operatively, although adjuvant chemotherapy is recommended in some case reports [7,12,13,15]. In our group, postoperative adjuvant chemotherapy was recommended for all patients, but compliance was not high.…”
Section: Discussionmentioning
confidence: 80%
“…However, Kawamura et al demonstrated that the superficial system may be more pertinent in the evolution of axillary lymph node involvement as the abdominal wall superior to the umbilicus drains upwards into the axillary nodes [13]. Unlike published reports of involvement of the left breast in 55% of cases, this patient's metastatic lesion occurred on the right breast, but similar to documented cases, her breast lesion was superficial, located in the upper outer quadrant, was mobile and fell within the reported size range (between 1 and 10 cm) [3] [12].…”
Section: Discussionmentioning
confidence: 99%
“…However, individual case reports suggest that some patients may potentially achieve long-term survival. A case report by Imaizumi et al documented a nine-year survival between the time of initial diagnosis of colon cancer and axillary lymph node recurrence, suggesting that tumour biology may influence the metastatic potential in such cases [13]. Traditionally, the treatment of metastatic disease is based on the pathogenesis and biology of the primary tumour.…”
Section: Immuno-histochemical Analysis Confirms the Final Diagnosismentioning
confidence: 99%
“…This route is typically seen in cases of colon cancer with abdominal wall invasion. [4][5][6][7] Moreover, colon cancer may metastasize to the breast before spreading to the axillary lymph node. 8 Concurrent metastasis to the right axillary lymph nodes in ascending colon cancer has not been reported previously.…”
Section: Figurementioning
confidence: 99%
“…Another possible pathway for axillary lymph node metastasis is through the superficial abdominal lymphatics, which establish lymphatic drainage channels between the abdominal wall and the thoracic wall, allowing colon cancer to reach the axillae bilaterally. This route is typically seen in cases of colon cancer with abdominal wall invasion 4–7 . Moreover, colon cancer may metastasize to the breast before spreading to the axillary lymph node 8 .…”
mentioning
confidence: 99%